2009
DOI: 10.1038/ismej.2009.137
|View full text |Cite
|
Sign up to set email alerts
|

Microtoming coupled to microarray analysis to evaluate the spatial metabolic status of Geobacter sulfurreducens biofilms

Abstract: Further insight into the metabolic status of cells within anode biofilms is essential for understanding the functioning of microbial fuel cells and developing strategies to optimize their power output. Cells throughout anode biofilms of Geobacter sulfurreducens reduced the metabolic stains: 5-cyano-2,3-ditolyl tetrazolium chloride and Redox Green, suggesting metabolic activity throughout the biofilm. To compare the metabolic status of cells growing close to the anode versus cells in the outer portion of the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
104
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(119 citation statements)
references
References 58 publications
11
104
4
Order By: Relevance
“…Type IV (PilA) pili of G. sulfurreducens are an essential component of the conductive anode biofilm, promoting cell-to-cell electron transfer through the 50-m-thick biomass layer (18,39,45,56,63). The biofilms are electrically conductive, and the evidence is consistent with type IV pili functioning as the final electron con- duit onto insoluble Fe(III) oxide (53).…”
Section: Discussionmentioning
confidence: 56%
“…Type IV (PilA) pili of G. sulfurreducens are an essential component of the conductive anode biofilm, promoting cell-to-cell electron transfer through the 50-m-thick biomass layer (18,39,45,56,63). The biofilms are electrically conductive, and the evidence is consistent with type IV pili functioning as the final electron con- duit onto insoluble Fe(III) oxide (53).…”
Section: Discussionmentioning
confidence: 56%
“…A novel technique that allowed spatial transcriptional profiling of the current producing biofilm indicted that there was no significant difference in metabolism between the cells closet to the anode and those furthest from the electrode surface [129]. Gene expression patterns suggest that the cells closet to the anode surface, while metabolic active, expressed a range of proteins commonly associated with environmental stress, expected to be a result of the proton accumulation.…”
Section: Proton Inhibition In Microbial Fuel Cell Biofilmsmentioning
confidence: 99%
“…A decrease in the pH of the bulk fluid of a MFC has been shown to decrease power production [83,126]. Modeling studies predicted that proton accumulation would lead to zones of metabolic inactivity within the biofilm [127], but metabolic staining indicated activity throughout the entire biofilm [128,129].…”
Section: Proton Inhibition In Microbial Fuel Cell Biofilmsmentioning
confidence: 99%
“…Furthermore, in a study observing differences between current consuming versus current producing cells, the gene GSU2732 was found in higher abundance in current producing cells [183], a finding supported by a previous study showing the gene to be expressed in current producing cells [35]. In a study comparing the metabolic status of cells growing close to an anode electrode versus cells in the outer portion of the anode biofilm, the gene GSU2743 a homologue of KN400_2682 was found to be decreased in the outer biofilm and was said to not play a direct role in EET [184]. A study observing the proteins involved in electron transfer between Fe(III) and Mn(IV) oxides as well as a soluble electron accepter Fe(III) citrate found that the genes GSU2732 (KN400_2674) and PgcA had higher transcript levels higher on growth on Mn(IV) oxide vs soluble Fe(III) citrate however this was not the case with Fe(III) oxide [185].…”
Section: Abundance Of Eet Related Proteinssupporting
confidence: 66%